2014
DOI: 10.7150/ijms.7405
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic CpG Methylation Biomarkers Identified by Methylation Array in Esophageal Squamous Cell Carcinoma Patients

Abstract: Background: Esophageal squamous cell carcinoma (ESCC) is an aggressive cancer with poor prognosis. We aimed to identify a panel of CpG methylation biomarkers for prognosis prediction of ESCC patients.Methods: Illumina's GoldenGate methylation array, supervised principal components, Kaplan-Meier survival analyses and Cox regression model were conducted on dissected tumor tissues from a training cohort of 40 ESCC patients to identify potential CpG methylation biomarkers. Pyrosequencing quantitative methylation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 27 publications
(29 reference statements)
2
31
0
Order By: Relevance
“…Similarly, Shaffer et al [22] demonstrated that extensive methylation of the FES promoter contributes to inhibition of FES expression in colorectal cancer cells. In addition, Kuo et al [23] showed that the high methylation level of FES is a biomarker for prognosis prediction in esophageal squamous cell carcinoma patients, via risk score analysis. In addition, the methylation level of FES is positively related with tumor stage in breast cancer [24].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Shaffer et al [22] demonstrated that extensive methylation of the FES promoter contributes to inhibition of FES expression in colorectal cancer cells. In addition, Kuo et al [23] showed that the high methylation level of FES is a biomarker for prognosis prediction in esophageal squamous cell carcinoma patients, via risk score analysis. In addition, the methylation level of FES is positively related with tumor stage in breast cancer [24].…”
Section: Discussionmentioning
confidence: 99%
“…These data confirm the clinic-pathological and prognostic significance of SOX1 expression, and, to our knowledge, it is the first evidence of high SOX1 expression level as a negative prognostic biomarker in cancer. In fact, low expression of SOX1 protein and/or mRNA expression was correlated with shorter overall survival and poor prognosis in ovarian cancer22, human hepatocellular carcinoma2345, and esophageal squamous cell carcinoma4647. These two sets of observations are not conflicting per se because it is conceivable that the expression of SOX1 could be elevated or decreased depending on the epigenetic status or the cellular heterogeneity and plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…Schmidt et al recently proposed quantitative measurement of methylated SHOX2 DNA in plasma as a useful tool to monitor therapy response in advanced stage lung cancer patients [36]. Furthermore, an increased methylation level of SEPT9 was a predictor of poor prognosis in esophageal squamous cell carcinoma, as well as in prostate cancer on androgen deprivation [52, 53]. Likewise, colorectal cancer patients with high SEPT9 serum methylation levels at 1-year follow-up were found to be at high risk of disease recurrence [64].…”
Section: Discussionmentioning
confidence: 99%